Direct fabrication of inclined thin-walled parts by exploiting inherent overhanging capability of CMT process. Issue 3 (4th December 2019) - Zhao, Yun; Li, Fang; Chen, Shujun; Lu, Zhenyang
Abstract : Purpose: The purpose of this paper is to develop a build strategy for inclined thin-walled parts by exploiting the inherent overhanging capability of the cold metal transfer (CMT) process, which release wire-arc additive manufacturing from tedious programming work and restriction of producible size of parts. Design/methodology/approach: Inclined thin-walled parts were fabricated with vertically placed welding torch free from any auxiliary equipment. The inclined features were defined and analyzed based on the geometrical model of inclined parts. A statistical prediction model was developed to describe the dependence of inclined geometrical features on process variables. Based on these models, a build strategy was proposed to plan tool path and output process parameters. After that, the flow work was illustrated by fabricating a vase part. Findings: The formation mechanism and regulation of inclined geometrical features were revealed by conducting experimental trials. The inclined angle can be significantly increased along with the travel speed and offset distance, whereas the wall width is mainly dependent on the ratio of wire feed speed to travel speed. In contrast to other welding process, CMT has a stronger overhanging capability, which provides the possibility to fabricate parts with large overhanging features directly with high forming accuracy. Originality/value: This paper describes a novel build strategy for inclined thin-walled parts free from any auxiliary equipment. With the proposed strategy, a complex structural component can be deposited directly in the rectangular coordinates additive manufacturing system, indicating infinite possibilities on the producible size of the parts. Moreover, equipment requirements and tedious program work can also be significantly reduced.